Tools and Algorithms for the Construction and Analysis of Systems 24th International Conference, TACAS 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings, Part I - Beyer, Dirk; Huisman, Marieke (Theoretical Computer Science and General Issues,, 2018)
This book is Open Access under a CC BY licence. .